The Effect of the Emergence of Fintech on the Financial Performance of the Banking Sector: A Case Study Using ROA, LDR, and CAR Ratios - Hidayat, Arief; Rustandi Kartawinata, Budi (The International Journal of Business Review (The Jobs Review), 2023)
The future business model of the Indonesian banking sector is determined by the development of information technology in the course of the digital revolutions. Recognizing the importance of this matter, this study aims to analyze the financial performance of the banking sector before and after the emergence of financial technology (fintech) companies. The study uses financial ratios, including return on assets (ROA), loan to deposit ratio (LDR), and capital adequacy ratio (CAR), to measure the performance of banks. Overall, the study suggests that the emergence of fintech has brought both challenges and opportunities for the banking sector.